Breast cancer genes and the gendering of knowledge : science and citizenship in the cultural context of the "new" genetics - Gibbon, Sahra (Palgrave MacMillan, 2007)
The book examines the social and cultural context of new genetic knowledge associated with breast cancer. It looks at how this knowledge and technologies are used and received in two contrasting social arenas - cancer genetic clinics and a breast cancer research charity.